Visions of Canada : the Alan B. Plaunt memorial lectures, 1958-1992 - Ostry, Bernard, 1927-; Yalden, Janice (Published for Carleton University by McGill-Queen's University Press, 2004)
Contributors include Jacob Viner, F.R. Scott, Jean-Charles Falardeau, Harry Johnson, J.A. Corry, James Eayres, Kenneth Hare, Scott Gordon, Jane Jacobs, Maurice Strong, Mordecai Richler, John Hirsch, Guy Rocher, Charles Taylor, Stanley Roberts, Michael Kirby, John Meisel, Sylvia Ostry, Larkin Kerwin, Peter Lougheed, Mel Hurtig, Allan Gotlieb, Lise Bissonnette, and Bernard Ostry.